The Application of Artificial Intelligence (AI) In Optimizing Energy Consumption in Real Estate Projects: A Review - IFEDIORA Christian Osita; MAKATA Innocent Franklin; IGWENAGU Chukwudi Louis; IDHOLO Ingonabo Owolabi; CHUKWUMA Isioma Elizabeth (Journal of Current Research and Studies, 2025)
This review focused on the application of artificial intelligence (AI) in optimizing energy consumption in real estate projects, it noted that the real estate sector is a major contributor to global energy consumption which accounts for approximately 40% of total energy usage. To cater for the above emerged Artificial intelligence (AI) which appears as a promising solution to optimize energy consumption in real estate projects. The review identified the AI technologies which include machine learning and deep learning, can also aid in the analysis of the complex data patterns, prediction of energy demand and optimization energy distribution. It noted that the integration of AI in energy systems has revolutionized the way we approach energy optimization and its management systems can help in energy consumption optimization, reduction of waste and costs and minimisation of environmental impact. The research noted that the benefits of AI-powered energy optimization are multifaceted which includes energy savings, reduction of cost as well as environmental benefits. It also identified challenges and limitations to such as ensuring data quality and availability, cybersecurity, its scalability and interoperability. The identified case studies also demonstrated the effectiveness of AI-powered energy management systems in smart buildings and cities. The review concluded that the adoption of AI-powered energy optimization can help the real estate industry in term of reduction energy consumption, costs and environmental impact while also in the improvement occupant comfort and sustainability.